Estimation of Wave Condition Number From Pressure Waveform Alone and Its Changes With Advancing Age in Healthy Women and Men - Pahlevan, Niema M.; Mazandarani, Sohrab P. (Frontiers in Physiology, 2020)
Introduction: The wave condition number (WCN) is a non-dimensional number that determines the state of arterial wave reflections. WCN is equal to HR x Leff/PWV where HR, Leff, and PWV are the heart rate, effective length, and pulse wave velocity respectively. It has been shown that a value of WCN=0.1 indicates the optimum state of arterial wave reflection in which left ventricle workload is minimized. The pressure wave, flow wave, and PWV are all required to compute WCN, which may limit the potential clinical utility of WCN. The aims of this study are as follows: 1) to assess the feasibility of approximating WCN from the pressure waveform alone (WCNPinf), and 2) to provide the proof-of-concept that WCNPinf can capture age related differences in arterial wave reflection among healthy women and men. Methods: Previously published retrospective data composed of seventeen patients (age 19-54 years; 34.3±9.6) were used to assess the accuracy of WCNPinf. The exact value of WCN was computed from PWV (measured by foot-to-foot method), HR, and Leff. A quarter wavelength relationship with minimum impedance modulus were used to compute Leff. WCNPinf was calculated using HR and the reflected wave arrival time. Previously published analyses from a healthy subset of the Anglo-Cardiff Collaborative Trial (ACCT) study population were used to investigate if noninvasive WCNPinf captures age related differences in arterial wave reflection among healthy women and men. Results: A strong correlation (r = 0.83, p-value<0.0001) between WCNPinf and WCN was observed. The accuracy of WCNPinf was independent from relevant physiological parameters such as PWV, pulse pressure (PP), and HR. Similar changes in WCNPinf with advancing age were observed in both healthy men and healthy women. In young, healthy individuals (women and men) the WCNPinf was around 0.1 (the optimum value), and reduced with aging. Conclusion: WCN can be approximated from a single pressure waveform and can capture age related arterial wave reflection alteration. These results are clinically significant since WCN can be extracted from a single noninvasive pressure waveform. Future studies will focus on investigating if WCN is associated with risk for onset of cardiovascular disease events.